Hubungan antara Kelestarian Ekonomi dan Lingkungan: Suatu Kajian Literatur - Heri Sukendar W (Binus Business Review, 2013)
Pollution of the environment faced is generally caused by economic activity. Traditional economic theory placed trade-off between economic growth and environmental quality. However, since the early 1990s the empirical literature and theoretical literature have been growing rapidly. Research has shown that the relationship between economic growth and the environment can be positive. Research has shown the effect of income on environmental sustainability, control of population density. However, environmental pollution can be controlled to obtain optimal pollution which gives the maximum net benefits of economic activity. Identification of contaminants is required when optimal pollution can be determined. Economic instruments can be used to sue the polluters to control their economic activities. Selection of economic instruments that will be applied will work fine if the value of environmental contamination is known. In fact, pollution is not valuable, and therefore, the economic valuation of pollution is required. Several assessment techniques have been introduced, based on the type of pollution. The results also show that the conventional wisdom focuses more on the pollution control, in which they must be combined with the development of policy options that focus on ecoefficiency aspects of environmental sustainability and innovation in the process of economic development. If not, the economic growth will continue to degrade the environment in most countries.